2020
DOI: 10.22437/bio.v6i4.8958
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analisis Efektivitas Penggunaan Media Pembelajaran Digital Dalam Peningkatan Hasil dan Minat Belajar Biologi Peserta Didik di Era Revolusi Industri 4.0

Abstract: The nervous system in humans is a learning material that contains some abstract material and cannot be observed directly by students. The purpose of this study is to conduct an analysis of the use of digital learning media on nervous system learning materials and find out the types of learning media that can improve student learning outcomes and interests in the nervous system material. The method used is a meta-analysis by analyzing articles published in national journals related to digital-based learning med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
1
0
3
Order By: Relevance
“…Learning media that are effective in improving learning outcomes and students' interest in nervous system material use Augmented Reality (AR) media. (Hafzah et al, 2020) Nurwahidah, Nada Nupus Ihwani, Nadila Sofia, Riska With the title Utilization of Digital Media on Interest in Learning the Koran in Students, the results of the study can be concluded that learning media can increase and direct children's attention so that it can lead to learning motivation, more direct interaction between students and their environment, and the possibility for students to learn independently according to their abilities and interests. The media used in learning can make it easier for children and increase their motivation or fondness for reciting; that is, they can use digital media.…”
Section: Resultsmentioning
confidence: 99%
“…Learning media that are effective in improving learning outcomes and students' interest in nervous system material use Augmented Reality (AR) media. (Hafzah et al, 2020) Nurwahidah, Nada Nupus Ihwani, Nadila Sofia, Riska With the title Utilization of Digital Media on Interest in Learning the Koran in Students, the results of the study can be concluded that learning media can increase and direct children's attention so that it can lead to learning motivation, more direct interaction between students and their environment, and the possibility for students to learn independently according to their abilities and interests. The media used in learning can make it easier for children and increase their motivation or fondness for reciting; that is, they can use digital media.…”
Section: Resultsmentioning
confidence: 99%
“…Terdapat 7 dari 14 artikel yang dilakukan meta-analisis menggunakan jenis penelitian pengembangan (Surata et al, 2020). Adapula 10 artikel yang dilakukan metaanalisis media pembelajaran terhadap hasil dan minat belajar biologi (Hafzah et al, 2020). Sehingga dapat diketahui bahwa masih minimnya informasi dan penelitian mengenai Pengaruh media e-learning terhadap keterampilan berpikir kritis didominasi oleh Pulau Jawa.…”
Section: Augmented Realityunclassified
“…Penelitian meta-analisis selanjutnya, menunjukkan bahwa penggunaan media multimedia memiliki pengaruh yang tinggi terhadap pembelajarn biologi (Surata et al, 2020). Penelitian meta-analisis lainnya, menunjukkan bahwa media pembelajaran berbasis digital berpengaruh terhadap minat dan hasil belajar peserta didik (Hafzah et al, 2020). Beberapa penelitian meta-analisis tersebut dapat diketahui bahwa belum ada penelitian meta-analisis mengenai pengaruh media e-learning terhadap keterampilan berpikir abad 21 khususnya keterampilan berpikir kritis dan kreatif.…”
unclassified
“…Kondisi pembelajaran biologi saat ini khususnya pada topik yang bersifat abstrak, materi biasanya hanya diajarkan melalui buku cetak dan LKS sehingga kondisi demikian membuat siswa kurang tertarik dan termotivasi (Hafzah et al, 2020). Selain hal tersebut cakupan materi biologi banyak yang membutuhkan tampilan gambar dan animasi kurang dapat dimaksimalkan yang berdampak pada kurang semangatnya siswa dalam mengikuti pembelajaran (Hadijah, 2020).…”
Section: A Pendahuluanunclassified